1984
DOI: 10.1021/bi00320a035
|View full text |Cite
|
Sign up to set email alerts
|

Monovalent cation-induced phospholipid vesicle aggregation: effect of ion binding

Abstract: Aggregation of acidic phospholipid vesicles induced by monovalent cations was studied for vesicles of small and large sizes. It was found that there were two phases in the aggregation of large acidic phospholipid vesicles. In the initial phase, observed in the range of 0.1-0.4 M monovalent salts, aggregation took place spontaneously after a change in salt concentration; in the second phase (greater than 0.4 M salt), aggregation progressed gradually with time. The order of capability for monovalent cations to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…The vesicles were added to the Teflon bath (0.8 cm in diameter) and mixed with Ca-free buffer solution (MOPS/KCl 5/250 mM, pH 7.4) and S-layer protein (0.2 mg/ml). Then a monolayer was formed by spreading a chloroform solution (1.5 l of a 5 mg/ml lipid DPhPC:DPhPE 7:3 mol ratio) on the bath solution in order to allow vesicle fusion and the formation of a bilayer [36]. After 1 h, 0.4 l of a 1 M CaCl 2 solution was added to initiate the S-layer self-assembly process.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…The vesicles were added to the Teflon bath (0.8 cm in diameter) and mixed with Ca-free buffer solution (MOPS/KCl 5/250 mM, pH 7.4) and S-layer protein (0.2 mg/ml). Then a monolayer was formed by spreading a chloroform solution (1.5 l of a 5 mg/ml lipid DPhPC:DPhPE 7:3 mol ratio) on the bath solution in order to allow vesicle fusion and the formation of a bilayer [36]. After 1 h, 0.4 l of a 1 M CaCl 2 solution was added to initiate the S-layer self-assembly process.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…In addition, metal ions are known to considerably affect the colloidal behavior of phospholipids and bile salts respectively [10][11][12][13]. Tanaka et al [11] found that very low concentration of La 3+ and Gd 3+ induced a shape change of giant unilamellar vesicles of phosphatidylcholine.…”
Section: Introductionmentioning
confidence: 99%
“…Tanaka et al [11] found that very low concentration of La 3+ and Gd 3+ induced a shape change of giant unilamellar vesicles of phosphatidylcholine. Ohki et al [12,13] reported the phenomena of monovalent and divalent cation-induced phospholipid vesicle aggregation. The complexation of metal ions by bile salts in aqueous solution also has been investigated [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…With the aid of this new method, we have succeeded in preparing liposomes with a significantly high trapping efficiency for water-soluble drugs with ease and in one step without using toxic organic solvent [36][37][38][39] . Meanwhile, various kinds of phospholipids with different chemical structures are found in the natural world [40][41][42] and the effects are still unknown of the chemical structure of hydrophobic groups of these phospholipids on the formation and properties of liposomes prepared by the scCO 2 RPE method.…”
mentioning
confidence: 99%